Spatial models of abundance and habitat preferences of commerson's and Peale's dolphin in southern patagonianwaters - Dellabianca, Natalia Andrea; Pierce, Graham J.; Raya Rey, Andrea Nélida; Scioscia, Gabriela; Miller, David L.; Torres, Monica Analia; Paso Viola, María Natalia; Prosser Goodall, Rae Natalie; Schiavini, Adrian Carlos Miguel (PLOS ONE)
Commerson's dolphins (Cephalorhynchus c.commersonii) and Peale's dolphins (Lagenorhynchus australis) are two of the most common species of cetaceans in the coastal waters of southwest South Atlantic Ocean. Both species are listed as Data Deficient by the IUCN, mainly due to the lack of information about population sizes and trends. The goal of this study was to build spatially explicit models for the abundance of both species in relation to environmental variables using data collected during eight scientific cruises along the Patagonian shelf. Spatial models were constructed using generalized additive models. In total, 88 schools (212 individuals) of Commerson's dolphin and 134 schools (465 individuals) of Peale's dolphin were recorded in 8,535 km surveyed. Commerson's dolphin was found less than 60 km from shore; whereas Peale's dolphins occurred over a wider range of distances from the coast, the number of animals sighted usually being larger near or far from the coast. Fitted models indicate overall abundances of approximately 22,000 Commerson's dolphins and 20,000 Peale's dolphins in the total area studied. This work provides the first large-scale abundance estimate for Peale's dolphin in the Atlantic Ocean and an update of population size for Commerson's dolphin. Additionally, our results contribute to baseline data on suitable habitat conditions for both species in southern Patagonia, which is essential for the implementation of adequate conservation measures. Fil: Dellabianca, Natalia Andrea. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Pierce, Graham J. University Of Aberdeeen; Reino Unido. Universidade de Aveiro; Portugal Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Scioscia, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. ...